Porous oil-containing polymer material as well as preparation method and application thereof

By depositing a solid lubricating film on the surface of the porous polymer matrix and storing liquid lubricating, solid-liquid collaborative lubricating is achieved, and the friction and wear of porous oil-containing polyimide materials is solved when the lubricating oil is insufficient, and effective lubrication and friction wear are achieved.

CN119735855AActive Publication Date: 2025-04-01LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411930182.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing porous oil-containing polyimide materials cannot effectively reduce friction and wear when the lubricating oil supply is insufficient.

Method used

Solid-liquid collaborative lubrication is achieved by depositing a solid lubricating film on the surface of the porous polymer matrix and storing liquid lubricating oil in its pores. The material of the solid lubricating film can be diamond-like, graphene, molybdenum disulfide and black phosphorus, and the liquid lubricating oil can include PAO, Pegasus II, RIPP555 and Mobil gear oil.

Benefits of technology

When the lubricant oil supply is insufficient, the porous oil-containing polymer material can still achieve effective lubrication, significantly reducing friction and wear, and will not affect the storage, release and suction of lubricant oil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735855A_ABST
    Figure CN119735855A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lubrication, and provides a porous oil-containing polymer material as well as a preparation method and application thereof. The porous oil-containing polymer material comprises a porous polymer matrix, a solid lubricating film deposited on the porous polymer matrix, and liquid lubricating oil stored in pores of the porous polymer matrix deposited with the solid lubricating film. According to the invention, the solid lubricating film is deposited on the surface of the porous polymer matrix, and the liquid lubricating oil is adsorbed and stored, so that solid-liquid synergistic lubrication is realized, and the porous oil-containing polymer material can still be effectively lubricated and the frictional wear is reduced when the lubricating oil is insufficient in supply and the porous oil-containing polymer material is subjected to friction shear action in pairs. Meanwhile, the deposition of the solid lubricating film does not cause the blockage of the pore structure of the porous polymer matrix, and does not affect the storage, release and resorption of the lubricating oil; and the frictional wear of the porous oil-containing polymer material is obviously reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of lubrication technology, and in particular to a porous oil-containing polymer material and a preparation method and application thereof. Background Art

[0002] With the continuous progress and development of modern science and technology, the global demand for high-precision and cutting-edge technologies has increased year by year. Among them, porous oil-containing polyimide materials can store lubricating oil by utilizing their internal pore structure, and can realize self-circulating oil storage and supply without the need for external oil supply equipment. They have the characteristics of high precision, strong reliability, long service life and maintenance-free, and have important applications in aerospace and high-end equipment. Although porous oil-containing polyimide materials can form a lubricating film at the interface to reduce the friction and shearing effect of the dual on the porous oil-containing polyimide materials, when the lubricating oil supply of the porous oil-containing polyimide materials is insufficient, the friction and shearing effect between the dual and the porous oil-containing polyimide materials cannot be avoided, thereby causing friction and wear. That is, the lubrication performance of existing porous oil-containing polyimide materials needs to be further improved. Summary of the invention

[0003] In view of this, the purpose of the present invention is to provide a porous oil-containing polymer material and its preparation method and application. The porous oil-containing polymer material of the present invention can still achieve effective lubrication and reduce friction and wear when the lubricating oil supply is insufficient and the porous oil-containing polymer material is subjected to friction and shearing.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a porous oil-containing polymer material, comprising a porous polymer matrix, a solid lubricating film deposited on the porous polymer matrix, and liquid lubricating oil stored in pores of the porous polymer matrix on which the solid lubricating film is deposited;

[0006] The material of the solid lubricating film is one or more of diamond-like carbon, graphene, molybdenum disulfide and black phosphorus.

[0007] Preferably, the material of the porous polymer matrix includes one of polyimide, nylon, polyetheretherketone and polyphenylene sulfide.

[0008] Preferably, the porous polymer matrix has a pore size of 0 to 10 μm and a porosity of 0 to 50%, and both the pore size and the porosity are not zero.

[0009] Preferably, the thickness of the solid lubricating film is 0-3 μm, and is not zero.

[0010] Preferably, the liquid lubricating oil comprises one or more of base oil PAO, Pegasus II, RIPP555 and Mobil gear oil.

[0011] The present invention also provides a method for preparing the porous oil-containing polymer material described in the above technical solution, comprising the following steps:

[0012] providing a porous polymer matrix;

[0013] Depositing a solid lubricating film on the porous polymer matrix to obtain a porous polymer matrix with a solid lubricating film deposited thereon;

[0014] The porous polymer matrix with the solid lubricating film deposited thereon is immersed in liquid lubricating oil to obtain the porous oil-containing polymer material.

[0015] Preferably, when the material of the porous polymer matrix is ​​polyimide, the method for preparing the porous polymer matrix comprises the following steps:

[0016] hot-pressing the polyimide powder to obtain the porous polymer matrix;

[0017] The temperature of the hot pressing is 300-380° C., and the pressure is 6-20 MPa.

[0018] Preferably, when the material of the solid lubricating film is diamond-like carbon, the deposition method is plasma-assisted chemical vapor deposition.

[0019] Preferably, the impregnation temperature is 60-150° C., the time is 12-72 hours, and the impregnation is performed in a vacuum environment.

[0020] The present invention also provides the use of the porous oil-containing polymer material described in the above technical solution or the porous oil-containing polymer material prepared by the preparation method described in the above technical solution in the field of lubrication.

[0021] The present invention provides a porous oil-containing polymer material.

[0022] The present invention achieves solid-liquid synergistic lubrication by depositing a solid lubricating film on the surface of a porous polymer matrix and absorbing and storing liquid lubricating oil, so that the porous oil-containing polymer material can still achieve effective lubrication and reduce friction and wear when the lubricating oil supply is insufficient and friction shearing occurs on the porous oil-containing polymer material. At the same time, the deposition of the solid lubricating film will not cause the pore structure of the porous polymer matrix to be blocked, and will not affect the storage, release and reabsorption of the lubricating oil; it also significantly reduces the friction and wear of the porous oil-containing polymer material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The preparation method provided by the present invention is a flow chart;

[0024] Figure 2The Raman spectra of PPI-DLC-1.5 obtained in Example 2 and PI-DLC-1.5 obtained in Comparative Example 4 are shown;

[0025] Figure 3 This is a cross-sectional SEM image of PPI-DLC-1.5 obtained in Example 2;

[0026] Figure 4 This is the pore size distribution diagram of PPI-DLC-1.5 obtained in Example 2;

[0027] Figure 5 This is the mercury inlet and outlet curve of PPI-DLC-1.5 obtained in Example 2. DETAILED DESCRIPTION

[0028] The present invention provides a porous oil-containing polymer material, comprising a porous polymer matrix, a solid lubricating film deposited on the porous polymer matrix, and liquid lubricating oil stored in pores of the porous polymer matrix on which the solid lubricating film is deposited;

[0029] The material of the solid lubricating film is one or more of diamond-like carbon, graphene, molybdenum disulfide and black phosphorus.

[0030] Unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.

[0031] The porous oil-containing polymer material provided by the present invention includes a porous polymer matrix. In the present invention, the material of the porous polymer matrix preferably includes one of polyimide, nylon, polyetheretherketone and polyphenylene sulfide, and is specifically preferably polyimide. In the present invention, the pore size of the porous polymer matrix is ​​preferably 0-10μm, and the porosity is preferably 0-50%, and the pore size and porosity are not 0. In the present invention, the pore size of the porous polymer matrix is ​​further preferably 0.1-10μm, and is specifically preferably 0.1μm, 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm or 10μm. In the present invention, the porosity of the porous polymer matrix is ​​further preferably 0.1-50%, specifically preferably 0.1%, 1%, 5%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 48% or 50%.

[0032] The porous oil-containing polymer material provided by the present invention includes a solid lubricating film deposited on the porous polymer matrix. In the present invention, the material of the solid lubricating film is one or more of diamond-like carbon, graphene, molybdenum disulfide and black phosphorus, and is preferably diamond-like carbon (DLC). In the present invention, the thickness of the solid lubricating film is preferably 0 to 3 μm, and is not 0, further preferably 0.1 to 3 μm, more preferably 0.5 to 2.5 μm, and specifically preferably 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm.

[0033] The porous oil-containing polymer material provided by the present invention comprises a liquid lubricating oil stored in the pores of a porous polymer matrix deposited with a solid lubricating film. In the present invention, the liquid lubricating oil preferably comprises one or more of base oil PAO, Pegasus II, RIPP555 and Mobil gear oil, and is particularly preferably base oil PAO, and the base oil PAO preferably comprises PAO4 and / or PAO10.

[0034] In the present invention, the use of solid lubricating film and liquid lubricating oil realizes solid-liquid system lubrication. Compared with materials without solid lubricating film, the porous oil-containing polymer material of the present invention can still achieve effective lubrication and reduce friction and wear when the lubricating oil supply is insufficient and friction and shearing occur between the porous oil-containing polymer material.

[0035] The present invention also provides a method for preparing the porous oil-containing polymer material described in the above technical solution, comprising the following steps:

[0036] providing a porous polymer matrix;

[0037] Depositing a solid lubricating film on the porous polymer matrix to obtain a porous polymer matrix with a solid lubricating film deposited thereon;

[0038] The porous polymer matrix deposited with the solid lubricating film is immersed in liquid lubricating oil to obtain the porous oil-containing polymer material.

[0039] The present invention provides a porous polymer matrix.

[0040] In the present invention, when the material of the porous polymer matrix is ​​preferably polyimide, the method for preparing the porous polymer matrix preferably comprises the following steps:

[0041] The polyimide powder is hot pressed to obtain the porous polymer matrix. In the present invention, the temperature of the hot pressing is preferably 300-380°C, and is particularly preferably 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C or 380°C; the pressure is preferably 6-20MPa, and is particularly preferably 6MPa, 8MPa, 10MPa, 12MPa, 14MPa, 16MPa, 18MPa or 20MPa; the time is preferably 0.5-8h, and is particularly preferably 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h or 8h; after the hot pressing, the present invention preferably further comprises: removing the pressure to maintain the volume unchanged, and cooling naturally to obtain the porous polymer matrix.

[0042] After obtaining the porous polymer matrix, the present invention deposits a solid lubricating film on the porous polymer matrix to obtain a porous polymer matrix with the solid lubricating film deposited thereon.

[0043] In the present invention, when the material of the solid lubricating film is preferably diamond-like carbon, the deposition method is preferably plasma-assisted chemical vapor deposition (PACVD). In the present invention, the parameters of the plasma-assisted chemical vapor deposition preferably include: a vacuum degree of 4×10 -3 Pa, substrate bias is -690 V, pulse frequency is 40 kHz, and C2H2 flow rate is 260 sccm.

[0044] In the present invention, the thickness of the solid lubricating film is preferably 0-3 μm and not 0, more preferably 0.1-3 μm, more preferably 0.5-2.5 μm, specifically preferably 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm.

[0045] After obtaining the porous polymer matrix with the solid lubricating film deposited thereon, the present invention immerses the porous polymer matrix with the solid lubricating film deposited thereon in liquid lubricating oil to obtain the porous oil-containing polymer material.

[0046] In the present invention, the impregnation temperature is preferably 60-150°C, specifically preferably 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C; the time is preferably 12-72h, specifically preferably 12h, 18h, 24h, 30h, 36h, 42h, 48h, 54h, 60h, 66h or 72h; the impregnation is preferably carried out in a vacuum environment, and the vacuum degree of the vacuum environment is preferably 10-10000Pa, specifically preferably 10Pa, 100Pa, 1000Pa or 10000Pa.

[0047] After the impregnation is completed, the present invention preferably further comprises taking out the sample and wiping off the liquid lubricating oil on the surface of the sample to obtain the porous oil-containing polymer material.

[0048] When the porous polymer matrix is ​​a porous polyimide matrix (denoted as PPI), and the material of the solid lubricating film is diamond-like carbon (DLC), the preparation method provided by the present invention is as follows: Figure 1 As shown, specifically: first, a porous polyimide matrix PPI is provided, and then DLC is deposited on the surface of PPI to obtain a porous polyimide matrix deposited with a diamond-like carbon film, which is recorded as PPI-DLC; then the PPI-DLC is immersed in liquid lubricating oil, referred to as oil immersion. After the immersion is completed, the oil on the surface of the material is wiped off to obtain a porous oil-containing polymer material, which is recorded as OLPPI-DLC.

[0049] The present invention also provides the use of the porous oil-containing polymer material described in the above technical solution or the porous oil-containing polymer material prepared by the preparation method described in the above technical solution in the field of lubrication.

[0050] The present invention does not specifically limit the application mode of the porous oil-containing polymer material, and those skilled in the art may configure it according to actual needs.

[0051] The porous oil-containing polymer material provided by the present invention, its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0052] Example 1

[0053] Preparation method of OLPPI-DLC-0.5:

[0054] (1) The polyimide powder was hot-pressed at 300° C. and 8 MPa for 2 h, and then the pressure was removed to maintain the volume unchanged and the temperature was naturally cooled to obtain a porous polyimide matrix with a pore size of 7 μm and a porosity of 48%, which was recorded as PPI.

[0055] (2) Plasma-assisted chemical vapor deposition (parameters include: vacuum degree of 4×10 -3 Pa, substrate bias is -690 V, pulse frequency is 40 kHz, C2H2 flow rate is 260 sccm) on the surface of the porous polyimide substrate to deposit diamond-like carbon (DLC), and the thickness of the DLC film is 0.5 μm by plasma assisted chemical vapor deposition, and PPI-DLC-0.5 is obtained.

[0056] (3) PPI-DLC-0.5 was then immersed in a beaker containing PAO 10 at 150°C and a vacuum degree of 10,000 Pa for 12 h. It was then taken out of the beaker and excess PAO 10 on the surface was wiped off to obtain OLPPI-DLC-0.5.

[0057] Example 2

[0058] Preparation method of OLPPI-DLC-1.5:

[0059] (1) The polyimide powder was hot-pressed at 360° C. and 12 MPa for 1 h, and then the pressure was removed to maintain the volume unchanged, and the temperature was naturally cooled to obtain a porous polyimide matrix with a pore size of 2 μm and a porosity of 15%, which was recorded as PPI.

[0060] (2) Plasma-assisted chemical vapor deposition (parameters include: vacuum degree of 4×10 -3 Pa, substrate bias of -690 V, pulse frequency of 40 kHz, C2H2 flow rate of 260 sccm) was used to deposit diamond-like carbon (DLC) on the surface of a porous polyimide substrate. The thickness of the DLC film was 1.5 μm by plasma assisted chemical vapor deposition, and PPI-DLC-1.5 was obtained.

[0061] (3) PPI-DLC-1.5 was then immersed in a beaker containing PAO 10 at 80°C and a vacuum degree of 100 Pa for 72 h. It was then taken out of the beaker and excess PAO 10 on the surface was wiped off to obtain OLPPI-DLC-1.5.

[0062] Example 3

[0063] OLPPI-DLC-3.0 preparation method:

[0064] (1) The polyimide powder was hot-pressed at 380° C. and 20 MPa for 0.5 h, and then the pressure was removed to maintain the volume unchanged, and the temperature was naturally cooled to obtain a porous polyimide matrix with a pore size of 1 μm and a porosity of 9%, which was recorded as PPI.

[0065] (2) Plasma-assisted chemical vapor deposition (parameters include: vacuum degree of 4×10 -3 Pa, substrate bias is -690 V, pulse frequency is 40 kHz, C2H2 flow rate is 260 sccm) on the surface of the porous polyimide substrate to deposit diamond-like carbon (DLC), and the thickness of the DLC film is 3.0 μm by plasma assisted chemical vapor deposition, thus obtaining PPI-DLC-3.0.

[0066] (3) PPI-DLC-3.0 was then immersed in a beaker containing PAO 10 at 150°C and a vacuum degree of 1000 Pa for 12 h. It was then taken out of the beaker and excess PAO 10 on the surface was wiped off to obtain OLPPI-DLC-3.0.

[0067] Comparative Example 1

[0068] Preparation method of OLPPI-DLC-0:

[0069] (1) The polyimide powder was hot-pressed at 380° C. and 6 MPa for 1 h, and then the pressure was removed to maintain the volume unchanged, and the temperature was naturally cooled to obtain a porous polyimide matrix with a pore size of 9 μm and a porosity of 5%, which was recorded as PPI.

[0070] (2) Plasma-assisted chemical vapor deposition (parameters include: vacuum degree of 4×10 -3 Pa, substrate bias of -690 V, pulse frequency of 40 kHz, C2H2 flow rate of 260 sccm) was used to deposit diamond-like carbon (DLC) on the surface of a porous polyimide substrate. The thickness of the DLC film was 0 μm by plasma-assisted chemical vapor deposition, and PPI-DLC-0 was obtained.

[0071] (3) PPI-DLC-0 was then immersed in a beaker containing PAO 10 at 60°C and a vacuum degree of 10 Pa for 12 h. It was then taken out of the beaker and excess PAO 10 on the surface was wiped off to obtain OLPPI-DLC-0.

[0072] Comparative Example 2

[0073] Preparation of OLPI-DLC-0

[0074] (1) The polyimide powder was hot-pressed at 380° C. and 20 MPa for 2 h, and the temperature was lowered while maintaining the pressure to obtain a non-porous polyimide matrix with a pore size of 0 μm and a porosity of 0%, which was recorded as PI.

[0075] (2) Plasma-assisted chemical vapor deposition (parameters include: vacuum degree of 4×10 -3 Pa, substrate bias of -690 V, pulse frequency of 40 kHz, C2H2 flow rate of 260 sccm) was used to deposit diamond-like carbon (DLC) on the surface of a non-porous polyimide substrate. The thickness of the DLC film was 0 μm by plasma-assisted chemical vapor deposition, and PI-DLC-0 was obtained.

[0076] (3) PI-DLC-0 was then immersed in a beaker containing PAO 10 at 60°C and a vacuum degree of 100 Pa for 72 h. It was then taken out of the beaker and the excess PAO 10 on the surface was wiped off to obtain OLPI-DLC-0.

[0077] Comparative Example 3

[0078] Preparation of OLPI-DLC-0.5:

[0079] (1) The polyimide powder was hot-pressed at 370° C. and 16 MPa for 4 h, and the pressure was maintained while the temperature was lowered to obtain a non-porous polyimide matrix with a pore size of 0 μm and a porosity of 0%, which was recorded as PI.

[0080] (2) Plasma-assisted chemical vapor deposition (parameters include: vacuum degree of 4×10 -3 Pa, substrate bias is -690 V, pulse frequency is 40 kHz, C2H2 flow rate is 260 sccm) on the surface of a non-porous polyimide substrate to deposit diamond-like carbon (DLC), and the thickness of the DLC film is 0.5 μm by plasma assisted chemical vapor deposition to obtain PI-DLC-0.5.

[0081] (3) PI-DLC-0.5 was then immersed in a beaker containing PAO 10 at 100°C and a vacuum degree of 500 Pa for 12 h. It was then taken out of the beaker and excess PAO 10 on the surface was wiped off to obtain OLPI-DLC-0.5.

[0082] Comparative Example 4

[0083] Preparation of OLPI-DLC-1.5:

[0084] (1) The polyimide powder was hot-pressed at 350° C. and 12 MPa for 7 h, and the pressure was maintained while the temperature was lowered to obtain a non-porous polyimide matrix with a pore size of 0 μm and a porosity of 0%, which was recorded as PI.

[0085] (2) Plasma-assisted chemical vapor deposition (parameters include: vacuum degree of 4×10 -3 Pa, substrate bias of -690 V, pulse frequency of 40 kHz, C2H2 flow rate of 260 sccm) was used to deposit diamond-like carbon (DLC) on the surface of a non-porous polyimide substrate. The thickness of the DLC film was 1.5 μm by plasma-assisted chemical vapor deposition, and PI-DLC-1.5 was obtained.

[0086] (3) PI-DLC-1.5 was then immersed in a beaker containing PAO 10 at 120°C and a vacuum degree of 5000 Pa for 48 h. It was then taken out of the beaker and the excess PAO 10 on the surface was wiped off to obtain OLPI-DLC-1.5.

[0087] Comparative Example 5

[0088] Preparation of OLPI-DLC-3.0:

[0089] (1) The polyimide powder was hot-pressed at 340° C. and 20 MPa for 8 h, and the pressure was maintained while cooling to obtain a non-porous polyimide matrix with a pore size of 0 μm and a porosity of 0%.

[0090] (2) Plasma-assisted chemical vapor deposition (parameters include: vacuum degree of 4×10 -3 Pa, substrate bias is -690V, pulse frequency is 40kHz, C2H2 flow rate is 260sccm) on the surface of a non-porous polyimide substrate to deposit diamond-like carbon (DLC), and the thickness of the DLC film is 3.0μm by plasma assisted chemical vapor deposition, thus obtaining PI-DLC-3.0.

[0091] (3) PI-DLC-3.0 was then immersed in a beaker containing PAO 10 at 150°C and a vacuum degree of 10 Pa for 12 h. It was then taken out of the beaker and excess PAO 10 on the surface was wiped off to obtain OLPI-DLC-3.0.

[0092] The tribological performance test was carried out on a reciprocating friction and wear tribometer (UMT-3) in a ball-disk contact mode. A steel ball (GCr15, 3 mm) was selected as the counterpart of the friction test. The test was run for 2 h at 10 N and 11 Hz. The wear scar volume was measured by a 3D profilometer. The results are shown in Table 1.

[0093] Table 1 Summary of pore size, porosity and tribological properties of the embodiments and comparative examples

[0094] sample Pore ​​size (μm) Porosity (%) DLC thickness (μm) Friction coefficient <![CDATA[Wear amount (mm 3 )]]> Comparative Example 2 0 0 0 0.286 19.335 Comparative Example 3 0 0 0.5 0.195 24.564 Comparative Example 4 0 0 1.5 0.180 20.270 Comparative Example 5 0 0 3.0 0.175 18.512 Comparative Example 1 9 5 0 0.110 4.024 Example 1 7 48 0.5 0.062 1.823 Example 2 2 15 1.5 0.032 1.598 Example 3 1 9 3.0 0.039 1.624

[0095] It can be seen from Table 1 that under the same DLC film thickness, the tribological performance of the material with a porous structure is better than that of the non-porous material. For the case where the substrate is a porous polyimide substrate, under the condition of the presence of pores, the tribological performance of the material gradually improves with the increase of the DLC film thickness; after the DLC film thickness exceeds 1.5μm, it begins to deteriorate.

[0096] Figure 2The Raman spectra of PPI-DLC-1.5 obtained in Example 2 and PI-DLC-1.5 obtained in Comparative Example 4 are shown in Table 1. Figure 2 It can be seen that PPI-DLC-1.5 and PI-DLC-1.5 are both at 1500cm -1 The characteristic peak of DLC appears at , and the results show that the DLC solid lubricating film is successfully deposited on the surface of PI and PPI.

[0097] Figure 3 This is a cross-sectional SEM image of PPI-DLC-1.5 obtained in Example 2. Figure 3 It can be seen that a DLC solid lubricating film with a thickness of 1.5 μm is deposited on the PPI surface.

[0098] The pore size distribution and mercury inlet and outlet curves of PPI-DLC-1.5 obtained in Example 2 were tested by mercury intrusion porosimetry. The results are as follows: Figure 4 and Figure 5 As shown, Figure 4 This is the pore size distribution diagram of PPI-DLC-1.5 obtained in Example 2, Figure 5 The mercury inlet and outlet curves of PPI-DLC-1.5 obtained in Example 2 are shown in Table 2. Figure 4 and Figure 5 It can be seen that the deposition of DLC does not lead to pore blockage in PPI.

[0099] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A porous oil-containing polymer material, characterized in that: The invention comprises a porous polymer matrix, a solid lubricating film deposited on the porous polymer matrix, and a liquid lubricating oil stored in pores of the porous polymer matrix on which the solid lubricating film is deposited; The material of the solid lubricating film is one or more of diamond-like carbon, graphene, molybdenum disulfide and black phosphorus.

2. The porous oil-containing polymer material according to claim 1, characterized in that The material of the porous polymer matrix includes one of polyimide, nylon, polyetheretherketone and polyphenylene sulfide.

3. The porous oil-containing polymer material according to claim 1 or 2, characterized in that: The pore size of the porous polymer matrix is ​​0-10 μm, and the porosity is 0-50%. The pore size and porosity are not zero.

4. The porous oil-containing polymer material according to claim 1, characterized in that The thickness of the solid lubricating film is 0-3 μm, and is not zero.

5. The porous oil-containing polymer material according to claim 1, characterized in that: The liquid lubricating oil includes one or more of base oil PAO, Pegasus II, RIPP555 and Mobil gear oil.

6. The method for preparing the porous oil-containing polymer material according to any one of claims 1 to 5, characterized in that: The following steps are involved: providing a porous polymer matrix; Depositing a solid lubricating film on the porous polymer matrix to obtain a porous polymer matrix with a solid lubricating film deposited thereon; The porous polymer matrix with the solid lubricating film deposited thereon is immersed in liquid lubricating oil to obtain the porous oil-containing polymer material.

7. The preparation method according to claim 6, characterized in that: When the material of the porous polymer matrix is ​​polyimide, the preparation method of the porous polymer matrix comprises the following steps: hot-pressing the polyimide powder to obtain the porous polymer matrix; The temperature of the hot pressing is 300-380° C., and the pressure is 6-20 MPa.

8. The preparation method according to claim 6, characterized in that: When the material of the solid lubricating film is diamond-like carbon, the deposition method is plasma-assisted chemical vapor deposition.

9. The preparation method according to claim 6, characterized in that: The impregnation temperature is 60-150° C., the time is 12-72 hours, and the impregnation is performed in a vacuum environment.

10. Use of the porous oil-containing polymer material according to any one of claims 1 to 5 or the porous oil-containing polymer material prepared by the preparation method according to any one of claims 6 to 9 in the field of lubrication.

Citation Information

Patent Citations

  • Membrane-oil composite lubrication method

    CN105909963A

  • Solid-liquid composite lubricating system for reducing friction coefficient of moving part

    CN111621759A

  • Porous oil-containing intelligent lubricating material as well as preparation method and application thereof

    CN114149842A

  • Solid lubricating film for vacuum, its manufacturing method, and vacuum equipment

    JP2005350584A